2008
DOI: 10.2460/javma.233.12.1902
|View full text |Cite
|
Sign up to set email alerts
|

Use of trazodone as an adjunctive agent in the treatment of canine anxiety disorders: 56 cases (1995–2007)

Abstract: Although further controlled studies of dose range, efficacy, and safety are needed, trazodone may provide an additional therapeutic option for use in dogs that are unresponsive to conventional treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 34 publications
4
86
0
1
Order By: Relevance
“…Owner satisfaction and treatment success data. (Crowell-Davis et al, 2003;Cracknell and Mills, 2008;Gruen and Sherman, 2008;Herron et al, 2008;Ibanez and Anzola, 2009;Ogata and Dodman, 2011). One study has shown no statistically significant difference between dogs whose owners interacted with them during a storm and those that did not (Cottam et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Owner satisfaction and treatment success data. (Crowell-Davis et al, 2003;Cracknell and Mills, 2008;Gruen and Sherman, 2008;Herron et al, 2008;Ibanez and Anzola, 2009;Ogata and Dodman, 2011). One study has shown no statistically significant difference between dogs whose owners interacted with them during a storm and those that did not (Cottam et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Psychotropic medications including SSRIs Ibanez and Anzola, 2009), serotonin 2A antagonist/reuptake inhibitors (Gruen and Sherman, 2008), TCAs (Crowell-Davis et al, 2003), alpha-2 agonists (Ogata and Dodman, 2011), and benzodiazepines (Crowell-Davis et al, 2003;Herron et al, 2008;Ibanez and Anzola, 2009) have been studied as treatments for noise phobias and other situational anxieties in dogs. However, daily psychotropic medications including SSRIs and TCAs may have possible obstacles to success including a delayed onset of therapeutic effect of up to 4 weeks (Crowell-Davis and Murray, 2006) and the potential need for an additional situational medication (Crowell-Davis et al, 2003;Gruen and Sherman, 2008;Ibanez and Anzola, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MRZ orally administered in the dose range (1.88-3.75 mg/cat day) caused significant polyphagia in cats, this pharmacokinetic behaviour is different to that of human beings. In canine species, MRZ orally administered (at about 1 mg kg −1 ) showed a favourable pharmacokinetic profile (which is different to that in both cats and humans) compared to other CNS active drugs such as clomipramine (King et al, 2000), fluoxetine (Simpson et al, 2007) and trazodone (Gruen and Sherman, 2008). For these reasons, it was speculated (Giorgi, 2012) to be potentially useful for veterinary patients for treatment of anorexia and a wide range of anxiety-related conditions (Overall, 2000), for its antiemetic properties (due to antagonism of 5-HT 3 receptor) and as an analgesic in chronic and cancerassociated pain, due to its effects on both the noradrenergic and serotonic system (Bannister et al, 2009).…”
Section: Introductionmentioning
confidence: 92%